ANALISIS ASUHAN KEPERAWATAN GANGGUAN OKSIGENASI PADA PASIEN TN. S DENGAN DIAGNOSA MEDIS PPOK DI RUANG EDELWEIS ATAS RSUD KARDINAH - Jalu Satria Aji; Indri Heri Susanti (Jurnal Inovasi Penelitian, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is one of the health problems that occurs due to respiratory failure that occurs in geriatrics. The basic need for oxygenation is the most vital basic need in human life. One of the disturbances in oxygenation requirements is ineffective airway clearance. As a nurse, the health assistance that can be given to COPD patients with ineffective airway clearance is effective coughing. This study aims to determine the nursing care of oxygenation disorders in COPD patients with ineffective airway clearance problems in the Upper Edelweiss Room of Kardinah Hospital Tegal. This study uses a descriptive design in the form of a case study approach to nursing practice. This case study conducted an effective cough intervention for patients 3 times a day and with a duration of 5-10 minutes for 3x24 hours. The results showed that the problems that occurred in the client could be resolved on the 3rd day and which was characterized by a decreased respiratory rate (24 x/minute), no rales, and the patient was able to excrete phlegm